Study of materials for reactors employing molten fluoride salts or PB-BI coolant using an electron irradiation test facility - Azhazha, V.M.; Bakai, A.S.; Gurin, I.V.; Neklyudov, I.M.; Omelchuk, A.A.; Zelenskiy, V.F.; Garner, F.A. (Вопросы атомной науки и техники, 2005)
Overview of results obtained within the framework of the STCU Project #294 is given Наведено огляд результатів, отриманих в рамках проекту УНТЦ № 294. Приведен обзор результатов, полученных в рамках проекта УНТЦ № 294